2001
DOI: 10.1046/j.1365-294x.2001.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of the inbreeding grass weed Barren Brome (Anisantha sterilis) reveals genetic diversity at the within‐ and between‐farm scales

Abstract: Nine microsatellites were used to screen 131 samples of Barren Brome (Anisantha sterilis: synonym Bromus sterilis) collected from within the fields of three English farms [from Oxfordshire (Oxon), Leicestershire (Leics) and Wiltshire (Wilts)] and eight seeds taken from samples of each of 10 farms across England, UK. Most individuals (approximately 97%) were homozygous. Polymorphism occurred at all nine loci in all three farms sampled at the field scale, and at most loci for nine of the other 10 farm samples. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 36 publications
6
39
1
Order By: Relevance
“…Population genetic structure is strongly affected by the highly inbred nature of CL breeding systems (Sun 1999;Green et al 2001;Lu 2002). Although within-population molecular genetic diversity may be low, high levels of genetic differentiation can occur between populations (Godt and Hamrick 1998;Sun 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population genetic structure is strongly affected by the highly inbred nature of CL breeding systems (Sun 1999;Green et al 2001;Lu 2002). Although within-population molecular genetic diversity may be low, high levels of genetic differentiation can occur between populations (Godt and Hamrick 1998;Sun 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although within-population molecular genetic diversity may be low, high levels of genetic differentiation can occur between populations (Godt and Hamrick 1998;Sun 1999). It is likely that such species exist as genetically different inbred lines that occasionally outcross (Green et al 2001;Lu 2002). Significant quantitative genetic variation in life-history traits occurs among sibships in highly inbred species (Clay 1982;Cheplick and Quinn 1988;Charlesworth and Charlesworth 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its large size, taxonomic complexity, and wide geographic range, no comprehensive worldwide treatment of all species in Bromus exists, but many floristic treatments and keys of Bromus have been published for various geographic regions in the New World (e.g., Shear 1900;Wagnon 1952;Mitchell 1967;Soderstrom and Beaman 1968;Pinto-Escobar 1981Matthei 1986;Allred 1993;Pavlick 1995;Gutiérrez and Pensiero 1998;Planchuelo and Peterson 2000) and the Old World (e.g., Veldkamp et al 1991;Forde and Edgar 1995;Chen and Kuoh 2000;Spalton 2002bSpalton , 2004. Genetic variation within and among many species has been studied using data from isozymes (Kahler et al 1981;Ainouche et al 1995Ainouche et al , 1999Oja 1998Oja , 1999Oja , 2002aOja , b, 2007Bartlett et al 2002), as well as an array of DNA-based molecular techniques, including RAPDs and AFLPs (Ferdinandez et al 2001;Massa et al 2001;Puecher et al 2001;Ferdinandez and Coulman 2002) and microsatellites (Green et al 2001;Ramakrishnan et al 2002). A physical map of the chloroplast genome has been constructed for one species, B. inermis (Pillay 1993).…”
Section: Taxonomy and Classificationmentioning
confidence: 99%
“…Other authors believe that these groups are sufficiently distinct to be regarded as genera (e.g., Tsvelev 1976). No taxonomic consensus exists, and infrageneric taxa in Bromus are recognized currently as distinct genera (e.g., Catalán et al 1997;Green et al 2001;Spalton 2002bSpalton , 2004, subgenera (e.g., Acedo andLlamas 1999), or sections (e.g., Smith 1985b;Pavlick 1995;Planchuelo and Peterson 2000). The sectional classification of Smith (1970) has been followed by most recent North American authors, and is employed here, incorporating later modifications by Smith (1985a) and Scholz (1998); all species mentioned below are treated as species of Bromus.…”
Section: Taxonomy and Classificationmentioning
confidence: 99%
“…The close genetic association of these geographically scattered populations may be due to dispersal in crop seed. As found in other plant species (Green et al 2001;Hughes and Queller 1993;Teulet et al 2000), molecular analyses proved highly informative in assessing diversity in Echinochloa spp. Danquah et al (2002) observed a higher level of diversity using AFLPs and microsatellites than when using isozymes and/or RAPDs.…”
Section: Discussionmentioning
confidence: 70%